PERAN GURU DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERWAWASAN MULTIKULTURAL - Fauziah, Nur (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2012)
In the context of religious education, multicultural paradigm is the main foundation organizing of teaching and learning process. Religious education requires more than just curriculum transformation, it also changes in the religious perspective of an exclusive view into multicultural outlook, or at least to maintain the views and attitudes of an inclusive and pluralism. Realized or not, these groups are culturally and ethnically distinct advance religion, often the victims of racism and impact of the larger society. Therefore, Islamic religious education as a discipline which include the national education have a duty to inculcate awareness of the differences, considering Islam is the majority religion in Indonesia, the postscript is a multi religious country. Growing awareness of religious diversity, required in the new format in the Islamic religious education with teaching multicultural vision. Islamic religious education learning brings a multicultural vision of dialogic approaches to inculcate awareness of living together in diversity and difference. This learning is built on the spirit of equality relationships, mutual trust, mutual understanding and appreciating the similarities, differences and uniqueness, as well as interdepedensi. This is an innovation and an integral and comprehensive reform in charge of religious education that is free of prejudice, racism, ambiguous and stereotyping. Religious education provides recognition of multicultural vision of plurality, learning tool for cross-border encounters, and the indoctrination transform to dialogue.